Assessing and guiding young children's development and learning - McAfee, oralie; Leon, Deborah J. ; Bodrova Elena (Boston, 2016)
Assessing and Guiding Young Children's Development and Learning is designed to help teachers conduct authentic, early childhood, classroom-based assessment, interpret the information that's gathered, and ultimately use the information to plan responsive, supportive curriculum that ensures optimal learning for children, ages three to eight. The authors include coverage of the teacher's legal, ethical, and professional responsibilities in assessment; how to organise for summary assessment and formative assessment; how to understand standardised assessments; and how to communicate with parents. A special appendix helps teachers design assessments in all developmental domains and includes suggested behaviors to observe and charts to help teachers identify the next steps in learning and development. The 6th Edition has been revised and updated to reflect the rapidly developing concepts of appropriate assessment, expected educational outcomes, the way young children develop and learn, how the authentic assessment process relates to the use of formal state-mandated assessments, and the early childhood teacher's assessment responsibilities. -- Provided by publisher
Keywords: Classroom management; Early childhood education